Environmental impact of rock blasting activities on adjoining structures and its inhabitants: A case study of landson quarry in Ibadn (2011)
The impact of rock blasting activities on adjoining structures and on the health of the inhabitants was assessed by subjecting the inhabitants to administer structured questionnaire and response to simple questions concerning the state of their health. In addition, site reconnaissance survey, measurement of cracks on buildings and measurement of noise level were carried out. It was observed that the inhabitants are suffering from ailments traceable to the activities of the quarry in addition to general discomfort; the noise level being generated is approximately the same as the standard specified by the Federal Environmental Protection Agency. Also, it was discovered that the vibration generated from rock blasting is linked to some building collapse in the area while servicing ones are prone to collapse due to the high number of cracks on them. In conclusion, the sitting of quarry in residential area poses threats to both the structures and the people living in such area.